Pengaturan Peraturan Daerah Provinsi Nusa Tenggara Timur Nomor 7 Tahun 2020 Tentang Retribusi Izin Usaha Perikanan Dan Implementasinya - Anggrida Susana Li; Saryono Yohanes; Hernimus Ratu Udju (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Regional Taxes and Levies are one of the important sources of regional revenue to finance the implementation of Regional Government as regulated in NTT Provincial Regulation number 7 of 2020 concerning Fisheries Business License Levy. Regional Regulation of East Nusa Tenggara Province Number 7 of 2020 concerning Fisheries Business License Levy and Law No. 1 of 2022 concerning Financial Relations between the Central Government and Regional Governments gives authority to the Central and Regional Governments to collect Taxes and Regional Levies as a source of local revenue. One of the sources of the APBD comes from the Fishery Business Permit Levy. This is closely related to the collection of fishery business licenses. This research is a normative-empirical legal research that uses primary data and secondary data collected using interview, observation, and documentation techniques and processed using editing, coding, verification, and interpretation techniques and analyzed using qualitative descriptive techniques. The results of this study show that (1) The regulation of content material in NTT Provincial Regulation Number 7 of 2020 concerning Fisheries Business License Levy at Oeba Fish Market specifically related to the issuance of fishery business licenses and the collection of business license levies has been regulated in the NTT Provincial Regulation, the implementation strategy has not been implemented effectively. (2) Factors that hinder the regulation of East Nusa Tenggara Provincial Regulation Number 7 of 2020 concerning Fisheries Business License Levy and its implementation are legal factors and community legal awareness factors.